1995
DOI: 10.1007/bf01718429
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus papio 2, an SA8-like α-herpesvirus of baboons

Abstract: Several SA8 isolates obtained from baboons were compared to the prototype SA8 herpesvirus of African green monkeys. SDS-PAGE and restriction enzyme analyses revealed definite differences between green monkey and baboon isolates. DNA and amino acid sequences of the gB, gD and gJ glycoprotein genes exhibited substantial differences in variable regions. For the gB and gD, the amount of amino acid substitutions between SA8 and the baboon viruses was comparable to levels observed between analogous genes of SA8 & B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Furthermore, these results provide extensive supporting evidence that the genomes of HVP-2 and HSV are closely related. The results of these studies combined with previous genetic, pathogenic, and serologic analyses further demonstrate the close relationship between HVP-2 and HSV (Bigger & Martin, 2002;Eberle et al, 1995Eberle et al, , 1997Eberle et al, , 1998Levin et al, 1988).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Furthermore, these results provide extensive supporting evidence that the genomes of HVP-2 and HSV are closely related. The results of these studies combined with previous genetic, pathogenic, and serologic analyses further demonstrate the close relationship between HVP-2 and HSV (Bigger & Martin, 2002;Eberle et al, 1995Eberle et al, , 1997Eberle et al, , 1998Levin et al, 1988).…”
supporting
confidence: 57%
“…In 1985 an epizootic outbreak of a simplex-like virus occurred in a captive baboon colony (Eberle et al, 1995;Levin et al, 1988). The virus associated with this outbreak was serologically similar to simian herpesvirus SA8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For many years the baboon virus HVP2 was assumed to be identical to SA8 (9,11,12,17). However, more recent studies show that, while very closely related to SA8, baboon isolates represent a distinct virus (1,7). Similar to the case for BV in macaques, more than 90% of adult baboons show serological evidence of infection with HVP2, and clinically evident disease due to HVP2 is uncommon (6,27).…”
mentioning
confidence: 99%
“…Because of the similarity between HVP2 and the apathogenic SA8 and the lack of any reported human infections, baboon HVP2 has largely been considered unimportant from a zoonotic standpoint. However, during the production of immune-phase sera in mice, rapid-onset death was observed in mice inoculated intraperitoneally with one isolate of HVP2 (7). In a recent study comparing SA8 and HVP2 to HSV1 in a mouse model, two strains of HVP2 were found to readily invade the central nervous system (CNS) following peripheral intramuscular in-oculation (which most closely resembles a bite or scratch), producing paralysis and death (22).…”
mentioning
confidence: 99%